(untitled) (CIPEEX, 2023)
The present work presents an important part of the ’State of the Art’ scheduled for the preparation of a Master’s Thesis being developed in the stricto sensu Graduate Program in Environmental Sciences at the Evangelical University of Goiás (UniEVANGÉLICA). The agenda highlights the importance of studying/employing cultivars for the reduction of pesticide use in Brazil. To achieve success, a deductive approach was employed, enhanced by bibliographic and documentary techniques, which allowed for the development of descriptive research.